Acoustic heritage: community challenges in its safeguarding (2021)
Although there is no formal definition of acoustic heritage,it is commonly described as that heritage that contains the quantifiable acoustic parameters of the architectural and archaeological spaces of the past. Themain problem with this definition is that it assumes a direct, often artificial or unnecessary relationship between acoustic heritage, architectural heritage and archaeological heritage. However, this article tries todissociate them, proposing the acoustic heritage as an independent heritage. The approach addressed by this text is to relate acoustic heritage with intangible cultural heritage since the study of the quantifiableacoustic parameters of spaces yield relevant information on the use that communities give to their spaces and consequently the study of a collective inheritance.Due to its dependence on new technologies and its inherently dynamic nature, acoustic heritage has enormous potential to explore. In this context, this article aims to offer a contingent discussion on the need fortheir recognition, their safeguarding, the methodology involved in recording the acoustic heritage of active spaces and the primary role that the community should play in this process.